2007
DOI: 10.1007/s10461-007-9341-5
|View full text |Cite
|
Sign up to set email alerts
|

What You Think You Know Can Hurt You: Perceptual Biases About HIV Risk in Intimate Relationships

Abstract: The use of heuristic biases and the false consensus effect can lead individuals to misperceive risk of HIV infection. The current paper presents the results of two studies which sought to examine whether individuals, (a) weigh risk relevant information accurately in their assessments of HIV risk, and (b) are susceptible to the false consensus effect in their assessments of actual intimate partner risk behaviors. The results of the first study support the hypothesis that individuals do not use objective risk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(52 reference statements)
0
12
1
Order By: Relevance
“…Evidence for the influence of implicit or spontaneous processes on behavior is well established in studies on appetitive behaviors including substance use in particular (for review, see Ames et al, 2006; Stacy et al, 2010; Wiers & Stacy, 2006). Examples of research in implicit cognition and sexual behavior include sexual arousal (e.g., Gillath et al, 2007; Ponseti & Bosinski, 2010), sexual orientation (Snowden et al, 2008), implicit attitudes toward close interpersonal relationships (Baldwin et al, 2010), and assessment of HIV risk in romantic relationships (Harman et al, 2009). Only a few studies have examined the influence of implicit processes on HIV risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the influence of implicit or spontaneous processes on behavior is well established in studies on appetitive behaviors including substance use in particular (for review, see Ames et al, 2006; Stacy et al, 2010; Wiers & Stacy, 2006). Examples of research in implicit cognition and sexual behavior include sexual arousal (e.g., Gillath et al, 2007; Ponseti & Bosinski, 2010), sexual orientation (Snowden et al, 2008), implicit attitudes toward close interpersonal relationships (Baldwin et al, 2010), and assessment of HIV risk in romantic relationships (Harman et al, 2009). Only a few studies have examined the influence of implicit processes on HIV risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Kershaw, Ethier, Niccolai, Lewis and Ickovics (2003) identified a relationship between distortion of the perception of risk for HIV and the context of romantic relationships, in which underestimation of the risk was greater among adolescents in longer-lasting relationships. Harman, O'Grady and Wilson (2009) observed that women in long-term relationships evaluated their partners' sexual behaviors of risk inaccurately, and thought them to be similar to their own, underestimating, therefore, the risk of infection by HIV.…”
mentioning
confidence: 99%
“…Targeting factors associated with inaccurate perceptions about partner sexual risk may be an effective method of intervention. 13 STI prevention programs may therefore benefit by implementing interventions to improve relationship quality and sexual communication skills among young expecting parents. Prevention programs may also benefit by helping young expecting parents to identify and assess sources of information about their partner’s STI risk behavior and objectively evaluate their own and their partner’s STI risk.…”
Section: Discussionmentioning
confidence: 99%
“…13-15 However, research shows that couples may be strongly motivated to see their partner in ways that may not be valid. 16 Assumed similarity is particularly common in close relationships.…”
Section: Introductionmentioning
confidence: 99%